How Adversity Quotient and Work Stress Affect Work Procrastination? : Study of Hospital Nurses in Bandarlampung - Lis Andriani; Dicky Chandra; Habibullah Jimad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to ascertain how procrastination at work is impacted by adversity quotient and work stress. The issue in this study is whether procrastination at work might be influenced by one's adversity quotient and level of stress. This kind of study is known as casual research, which is a technique for looking at a variable's informal relationships. With a total of 100 responders, the nurses in Bandarlampung are the subject of this study. Multiple linear regression analysis utilizing SPSS software version 18 is the research methodology used in this study. The findings indicated that: 1) procrastination at work is negatively impacted by adversity quotient, and 2) procrastination at work is positively impacted by job stress. Researcher recommend that hospitals improve supervision and manage work-related stress for all nurses. It also recommend that nurses improve their capacity to handle a variety of issues by managing stress levels.